Discovery and evaluation of biphenyl derivatives of 2‐iminobenzimidazoles as prototype dual PTP1B inhibitors and AMPK activators with in vivo antidiabetic activity. (29th January 2023) - Babkov, Denis A.; Zhukovskaya, Olga N.; Brigadirova, Anastasia A.; Prilepskaya, Diana R.; Kolodina, Alexandra A.; Abbas, Abbas Haider S.; Morkovnik, Anatolii S.; Sobhia, M. Elizabeth; Ghosh, Ketan; Spasov, Alexander A.
Abstract: This work describes the synthesis of series hydrobromides of N ‐(4‐biphenyl)methyl– N ′‐dialkylaminoethyl‐2‐iminobenzimidazoles, which, due to the presence of two privileged structural fragments (benzimidazole and biphenyl moieties), can be considered as bi‐privileged structures. Compound 7a proved to activate AMP‐activated kinase (AMPK) and simultaneously inhibit protein tyrosine phosphatase 1B (PTP1B) with similar potency. This renders it an interesting prototype of potential antidiabetic agents with a dual‐target mechanism of action. Using prove of concept in vivo study, we show that dual‐targeting compound 7a has a disease‐modifying effect in a rat model of type 2 diabetes mellitus via improving insulin sensitivity and lipid metabolism. Abstract : Biphenyl derivative of 2‐iminobenzimidazole acts as a high‐micromolar AMPK activator and PTP1B inhibitor with a disease‐modifying effect in a rat model of type 2 diabetes mellitus via improving insulin sensitivity and lipid metabolism.